(3GdJegjO aj JfRjd GdaQhY Ydi GdbhGYO GdCUhdjIs - (3YHO GdQMje Hf GdMSf Hf Ydj GdESfhj GdTGaYj, CHh eMeO, LeGd GdOjf,J (B772 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eRjd CYPGQ GdeDdajf HEQTGO GdYbhd hJegjO GdCUhd hHYO , aEf CUhd Gdabg Yde YXje hbOQg hYdGTQag haNQg s
(3BNQgG (B:s
(3hcPG PcQ GdQGaYi ai cJGH GdbVGA hGddg CYde s
(3HG BKGQ JbWjYs
(3HgG fXGe GdJYbjHIs
(3cJHJ ef fSNI cJH eYXegG HNW GdeDda hcGf GdaQGZ efgG SfI (B768 s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs